PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PEMBANGUNAN - Quatro Thirtabrata, Audi; Rizki Windu Kencana, Ardhian; Desmawan, Deris (Populer: Jurnal Penelitian Mahasiswa, 2022)
Human capital is an important factor in economic development. With quality capital, it is believed that economic performance will also be better. So it can be said that "social development is economic development". The human resources of a nation, not physical capital or material resources, are the most determining factor in the character and speed of social and economic development of a nation concerned. UNDP's annual reports consistently show that human development promotes economic growth and economic growth that does not pay attention to human development will not last long. In order to run positively and sustainably, it must be supported by government social policies that are pro-human (social) development. Economic growth is defined as a process in which the productive capacity of an economy increases over time to produce ever greater levels of income.